A compact strain sensor based on M-shaped-core long-period fiber grating. (15th November 2022) - Su, Chunbo; Dai, Zizhao; Ma, Yiwei; Zhao, Min; Sun, Jing; Geng, Tao
Highlights: A highly sensitive strain optical fiber sensor is achieved by means of side-polishing and high-temperature oxyhydrogen flame heating. The highest strain sensitivity of the M-LPFG reaches to −19.05 pm/ με. A compact length is obtained, which is 5 mm. Low cost, simple structure and easy fabrication. Abstract: Optical sensors for strain measurement have been significantly concerned due to their unique characteristics of quick response, anti-electromagnetic interference and compact size. In this article, a brand-new type of "M"-shaped core long-period fiber grating (M-LPFG) based on core-modulated method is proposed and experimentally testified. By means of side-polishing and high-temperature oxyhydrogen flame heating, the cladding of fiber tends to be circular and the core will bend slightly towards the polished area. The micro-bending core is suffered strong refractive index modulation and this phenomenon also excites the evanescent field adequately. By analyzing the simulated light transmission and the transmission spectrum, considerable degree of micro-bending core is achieved. In the experiment, the proposed sensor with 10 periods (5 mm) displays a high strain sensitivity of −19.05 pm/ με with range of 0–500 με, and the temperature sensitivity of which is obtained as 51.16 pm/°C. Due to relatively small influence on cladding and self-circularity of structure, the M-LPFG possesses a high mechanical strength. With the above advantages of high sensitivity, compact size, low-cost and strong mechanical strength, the method of fabricating M-LPFG has great potential in strain measurement.